Kesejahteraan Sosial Ekonomi Masyarakat Duri di Tengah Social Distancing Pandemi Covid-19 - hary anto; mariatul fitri (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2019)
Social welfare aims to eliminate or reduce the pressures caused by socio-economic changes, avoid negative social consequences due to development and create conditions that can encourage increased community welfare. The corona pandemic that occurred became a scourge for the people of Duri city. The city of Duri is a diverse, pluralistic, or multiculturalistic society. Government regulations that require people to do social restrictions (social distancing) make hampered in the economic process of society. This study aims to (1) identify the impact caused by social distancing (2) steps taken by the community during the corona pandemic era. The approach of this research is descriptive qualitative. The data of this study is the impact of social distancing for the people of Kota Thorn. The data source comes from several communities in the City of Duri. Collecting data in this study using interview techniques, records, and continued notes. Data analysis in this study used an interactive method through three stages namely data reduction, data presentation, and drawing conclusions. The results showed (1) the impact caused by social restrictions (social distancing) for the community (2) steps taken by the community during the Covid-19 pandemic era.